The economic activity of women in families from different cultures - Jankiewicz, Jacek; Garsztka, Przemysław; Thakur, Jyoti (Research Papers in Economics and Finance, 2024)
The presented analysis uses data from time-use surveys which were conducted in India and Poland in the late 1990s and early 2000s. The calculations made use of statistical information describing individual households and their members. The applied method of multiple regressions for cross-sectional data made it possible to take into account selected socio-demographic and economic characteristics of the analysed members of the population. The results obtained served for assessing the impact of such characteristics as marital status, children presence on the production activity of women. We present the time allocation of individuals with similar characteristics, but at different stages of their life cycle.Performing analogous estimations for Poland and India made it possible to directly compare the situation of women in these countries. Despite considerable differences in terms of social and cultural norms between the analysed societies, the situation of women living in them is in some respects similar. However, marked differences were also observed such as those related to economic activity depending on the level of education. Also, the influence of marriage on the allocation of time is different, as illustrated by comparing the situation of married women to those without a partner.